Possible Interrelations of the Proto-slavic Concept of “Fool” with Initiation Rites and Magic Fairy Tales - Masliy, Olena (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2024)
In a series of publications, the second of which is this article, the author attempts to explore the phenomenon of conceptual memory as a type of collective memory and cultural memory, as well as a way of accumulating significant meanings.The theory of conceptual memory resonates with the linguistic theory of etymological (or cultural) memory of the words, which investigates the connections between the etymological and historical projections of a linguistic unit and its modern semantics. It seems that such connections can be observed between the original and ancient meanings of words and the concepts that they subsequently verbalize, tracing how language and culture preserve universal and unique meanings.To illustrate the theory of conceptual memory, the article demonstrates the interconnections of the hypothetical Proto-Slavic concept of “fool”, reconstructed in a previous work, with the initiation ritual and fairy tales. According to our hypothesis, the ancient concept of “fool” reflects the features of the initiation ritual and denotes the initiate himself. This is evidenced by the overlap of core and peripheral conceptual meanings with key moments of the initiation rite. Over time, the ritual is captured in initiation myths and other cultural texts, such as fairy tales.In new social realities, the tale gradually loses the understanding of its magical meanings of the ritual and presents a simplified and reinterpreted narrative of initiation, in which the concept of “fool” correlates primarily with the corresponding character. The conceptual meanings gradually take the form of a set of traits of the main fairy-tale hero, and the “fairy-tale background,” which reflects the features of the original ritual, ceases to be perceived as related to the concept.